Entrepreneurship & Community Involvement Project with IPMI Institute Students - Samuel PD Anantadjaya; Daniella CE Samuel; Irma M Nawangwulan; Abdul Haris Lahuddin; Sasotya Pratama; DC Ethan Samuel; Poetry Ken Savitri; Hari Ara Hariandja; Brian McNerney (Institut IPMI, 2025)
This explores the intersection of entrepreneurship and the Community Involvement Project (CIP) at IPMI Institute, focusing on the seminar held on May 23, 2025, where student groups presented solutions to community challenges, enhancing their analytical, collaborative, and public speaking skills. By examining the structure, objectives, and outcomes of the CIP, this highlights how IPMI’s approach bridges academic learning with societal impact, preparing students for leadership in national and international business contexts. The CIP is a cornerstone of IPMI’s curriculum, designed to empower students to apply entrepreneurial principles to address real world social challenges. In the CIP seminar showcased two student groups—Bank Sampah Group and Avoy Farm Group—who developed innovative solutions aligned with the United Nations Sustainable Development Goals (SDGs). By integrating market analysis, resource allocation, and impact assessment, the CIP fosters an entrepreneurial mindset, encouraging students to view challenges as opportunities for innovation and growth. The seminar provided a platform for students to refine their public speaking skills, presenting their findings to peers, lecturers, and industry professionals, thereby enhancing their ability to communicate complex ideas effectively. The CIP at IPMI Institute serves as a dynamic platform for fostering entrepreneurship and leadership through hands-on, community-focused initiatives. The seminar demonstrated the power of integrating academic rigor with practical application, as students tackled pressing social issues while honing their public speaking and analytical skills. By fostering collaboration, innovation, and effective communication, IPMI Institute prepares students to become impactful leaders in the global business arena. The success of projects like those presented by the Bank Sampah and Avoy Farm Groups highlights the potential of entrepreneurship to drive sustainable change. In addition, there are 3 more stands; the Amour de Cookies, HaZe Fragrance, and the Teboe ID. As IPMI Institute continues to refine its curriculum and expand its global partnerships, the CIP remains a vital tool for shaping future entrepreneurs who are not only business-savvy but also socially conscious and adept at engaging diverse audiences.